2013
DOI: 10.1186/1757-1146-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Provision of foot health services for people with rheumatoid arthritis in New South Wales: a web‐based survey of local podiatrists

Abstract: BackgroundIt is unclear if podiatric foot care for people with rheumatoid arthritis (RA) in New South Wales (NSW) meets current clinical recommendations. The objective of this study was to survey podiatrists’ perceptions of the nature of podiatric foot care provision for people who have RA in NSW.MethodsAn anonymous, cross-sectional survey with a web-based questionnaire was conducted. The survey questionnaire was developed according to clinical experience and current foot care recommendations. State registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…The current study revealed that most New Zealand podiatrists are not offering clinical sessions specifically for patients with rheumatic conditions. Similar findings have been reported in the UK [ 8 ] and Australia [ 13 ] and emphasize the widely occurring inadequacy in foot health provision for people with rheumatic conditions. It is possible that the lack of specific clinical sessions offered by New Zealand podiatrists is reflective of either an underestimation of the burden of foot involvement in rheumatic conditions, particularly given New Zealand’s comparatively small population or there is a lack of skills from podiatrists in managing people with rheumatic conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The current study revealed that most New Zealand podiatrists are not offering clinical sessions specifically for patients with rheumatic conditions. Similar findings have been reported in the UK [ 8 ] and Australia [ 13 ] and emphasize the widely occurring inadequacy in foot health provision for people with rheumatic conditions. It is possible that the lack of specific clinical sessions offered by New Zealand podiatrists is reflective of either an underestimation of the burden of foot involvement in rheumatic conditions, particularly given New Zealand’s comparatively small population or there is a lack of skills from podiatrists in managing people with rheumatic conditions.…”
Section: Discussionsupporting
confidence: 87%
“…We found that the majority of podiatrists received most referrals from GPs in comparison to other health professions. This referral tendency has also been found in Australia [ 13 ] and may reflect a good working relationship between podiatrists and GPs. The relatively low referral rates from other health professions may also be due to a lack of awareness of the podiatrist’s role by other health professionals.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Despite this, there appears to be a lack of access to podiatry services for PwRA and this has been consistently reported within the recent literature relative to the UK [34, 35] and other countries [13, 36]. Whilst new models of foot care for PwRA have been proposed [37, 38] further exploration of these is recommended for implementation of such strategies within routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Limited coverage of self-care activity and access to healthcare in the LFIS-RA may re ect the experiences of the study population, who were recruited from sites regarded to be centres of excellence in the UK with an international reputation and where podiatry is embedded into rheumatology services with specialised podiatry roles established. Therefore, the experience of foot care services in the patient cohort from which the LFIS-RA was derived may not be generalisable to Australia or New Zealand (or other countries), where a distinct lack of access to, and provision of, podiatry services and specialist rheumatology services in the public health system have been previously described [41][42][43].…”
Section: Discussionmentioning
confidence: 99%